Case Study and Evaluation of East Sumba Covid 19 Self-Isolation Sufferers - OBT Liunokas; Oktofianus Sila; Melkisedek Landi; Tri Maryati (Postgraduate, University of Mataram, 2023)
This research aims to analyze coordination, financing and field evaluation in carrying out Independent Isolation for handling Covid-19 Patients in East Sumba Regency. This method is a survey study, descriptive data analyzed in depth regarding the form of coordination, financing and evaluation in handling self-isolating patients in East Sumba Regency in 2022. The number of samples targeted is accidental sampling, namely samples that happened to be available at the time the research took place. The total sample was 99 people who were treated at home or in health facilities. The research results showed that there were 99 respondents, 54 people (54.34%) who had coordination going well and 45 people (45.66%) whose coordination did not go well. Controlling/supervision found 71 people (71.21%) were monitored and 29 people (28.79%) were not monitored/supervised, budgeting was funded by 62 people (62.50%) and 37 people (37.50%) did not receive funding and evaluation was 65 people (65.91%) and 34 people (34.09%) were not regularly evaluated by local health officials. East Sumba Covid-19 self-isolation sufferers with coordinated management, there is 46% no coordination, 29% of sufferers are not monitored, 37% do not receive costs and 34% are not evaluated